PENTINGNYA ETIKA DALAM PENDIDIKAN - RAFSEL TAS'ADI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The depelopment of technology in Globalization era may give bad influence to education nowadays. It had created people’s moral crisis, especially students. The changing of the students’ mentality and moral, for example, might be happened because of internal and/or external factors. The students never feel upset after doing something bad to others. They seemed that they did not know of how to respect adult people when doing communication. And, there were some other problems among the students. It might happen because they got lack of education about etique both at school or outside the school. The education of etique was really needed to do in order to solve those problems. It was clear that it became important thing in educational system today. The progress of education in one country, especially in Indonesia, could be seen from the suceed of implementing education characters to its students. One of the possible thing of changing character was through giving education of etique to them.Kata kunci: etika, pendidikan, guru, siswa